THE RESILIENCE OF BALI TRADITIONAL POTTERY CRAFTSMEN OF PEJATEN VILLAGE IN THE GLOBAL ERA - Gede Artayani, Ida Ayu; Ardika, I Wayan; Suarka, I Nyoman; Suwena, I Wayan (E-Journal of Cultural Studies; Volume 14, Number 1, February 2021DO - 10.24843/cs.2021.v14.i01.p01, 2021)
Pottery craftsmen in Pejaten Village still survive producing traditional pottery amid changes in their socio-cultural space. This study aims to analyze the reasons they persist in the realm of traditional pottery crafts today. This study uses the paradigm of critical thinking with a qualitative approach that views social reality as something that is intact, complex, dynamic, full of meaning with interactive symptom relationships. This research, analyzed by the generative structural theory of Pierre Bourdieu. Theory to explain the practice in the realm of pottery crafts in Pejaten Village. Bourdieu made a generative formula about practice, namely: (Habitus x Capital) + Domain = Practice. The results of this study indicate the survival practice of these pottery craftsmen by applying the habitus cutting strategy, in the form of intergenerational skills through informal education between families. Habitus they have internalized in individuals and make them have cultural capital. Ownership of cultural capital can be converted into other forms of capital, but the ability to convert capital cannot be done by all individuals, even though they grow and have a similar habitus. This is influenced by cognitive abilities, reasoning power, episteme, and individual experiences. This results in a class structure in the realm. Ownership of habitus and cultural capital is not sufficient to survive in this realm. Other capital ownership is needed, such as: economic capital, social capital, and symbolic capital. The results of this study can be used as a reference for developing the cultural sustainability of the traditional heritage between generations in responding to the changes that have occurred in the social space for pottery handicrafts in Pejaten Village today.  Keywords : sustainability, habitus, capital, traditional pottery craftsmen.